A Study of Asymptomatic Bacteriuria among Pregnant Women with and Without Gestational Diabetes Mellitus in Al-Jalla Gynecology Hospital, Tripoli, Libya - Abir Ben Ashur; Hamida El Magrahi; Asma Elkammoshi; Yomna Shomakhi; Wesal Alaawaj (AlQalam Journal of Medical and Applied Sciences, 2020)
Background. The infection of the urinary tract is one of the most significant reasons for seeking medical attention among individuals, and is one of the most widely common nosocomial infections. Gestational diabetes mellitus during pregnancy is considered an important risk factor for urinary tract infections. This study aims to investigate the prevalence of asymptomatic bacteriuria and the incidence of urinary tract infections in pregnant women with and without gestational diabetes mellitus and their antibiotic sensitivity patterns. Methods. Total of one hundred consecutive pregnant women with a clinical diagnosis of gestational diabetes mellitus (n=50) and non-diabetic pregnant women (n=50) were included in the study at Gynecology Hospital Tripoli, Libya. Mid-stream urine samples were obtained for a full urine examination. All samples and isolates were investigated by standard laboratory procedures. Asymptomatic bacteriuria was described as at least 105 CFU / ml growth isolated from a woman’s urine without complaints about urinary tract infections. Result. A total of 60 (60%) samples showed significant growth. No significant difference among the culture positivity rate was noted between gestational diabetic and non-diabetic patients (30% Vs 30%). Escherichia coli was the most frequent organism (50% in gestational diabetes mellitus and 43% non-diabetic) followed by staphylococcus aureus (27% in diabetic and 40% in non-diabetic). Ciprofloxacin (80%) was highly sensitive to infected bacteria. Conclusion. No significant differences in the prevalence of asymptomatic bacteriuria or incidence of urinary tract infections were found between pregnant women with and without gestational diabetes mellitus.